If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3n-9=0
We simplify the equation to the form, which is simple to understand
-3n-9=0
We move all terms containing n to the left and all other terms to the right.
-3n=0+9
We simplify left and right side of the equation.
-3n=+9
We divide both sides of the equation by -3 to get n.
n=-3
| 16m^4+9n^4=0 | | 375=4p-175 | | 8-7x=8(1+7x) | | (0.5*2.5)*x=3.5 | | 4(6-3)=94 | | -10=-9+x/4 | | 4x-3=1.72 | | r^3-11r^2+36r-36= | | 7m-6=65 | | 9-3r=2h | | -5(x-4)-3(-2-x)=x-2 | | 42+17r=-14r+-42 | | 4.2+2=10 | | 180=7x-13+2x+2+4x+9 | | 8=5-3x-6 | | X-5=2x-24 | | -25=5(w-7)-7w | | 4u^4+68u^2+280=0 | | 8=4-6b+2b | | 15=6-3n | | 72yp-12y= | | 5x+500=150 | | -9=3+5a-7 | | -4.9x^2+7.4x+10.9=0 | | 190=7x-13+2x+2+4x+9 | | 5y+13+5-3y=m | | 4(2y-4)=2(y-13) | | 60-(3c+4)=4c+24+c | | 14-6x= | | -4.9x^2+7.4t+10.9=0 | | Lne^2=6 | | 4+5(3x-x)=4(8+2x) |